Data for: An iterative approach to determine the refractive index of 3D printed 60GHz PLA lenses - Andreasson, Pererik (Halmstad University, 2019)
This study is a part of the research project eMC-Hammer. It describes an iterative approach to determine quasi-optical properties of standard 3D printer filament material to, in an inexpensive and fast way, construct focusing lenses for millimetre wave systems. Results from three lenses with different focal lengths are shown and discussed. The real part of the permittivity at 60GHz for polylactic acid (PLA) is in this paper determined to be er=2.74.

Purpose:

The purpose with the study is to validate an iterative, low cost, method of determining the refractive index of 3D printed lenses, where otherwise expensive equipment would be needed, such as S-parameter measurements using a vector network analyzer.

The dataset contains measurements, simulation results and matlab code used for the conference article "An iterative approach to determine the refractive index of 3D printed 60GHz PLA lenses" (doi:10.1049/cp.2018.1480)
See the conference article (methods) and lapc2018mainfigure.m (data description - meta data) for details.

Den här studien är en del av forskningsprojektet eMC-Hammer. Den beskriver ett iterativt tillvägagångssätt för att bestämma kvasi-optiska egenskaper hos standard 3D-skrivarfilamentmaterial för att, på ett kostnadseffektivt och snabbt sätt, kunna konstruera fokuseringslinser för millimetervågsystem. Resultatet för tre objektiv med olika brännvidd visas och diskuteras. Den verkliga delen av permittiviteten vid 60 GHz för polylaktid (PLA) är här bestämd att vara er = 2,74.

Syfte:

Syftet med studien är att validera en iterativ, kostnadseffektiv, metod för att bestämma brytningsindex på 3D-utskrivna linser, där annars dyr utrustning skulle behövas, till exempel S-parameter-mätningar med en vektornätverksanalysator.

Datasetet innehåller mätningar, simulationer och matlab-kod som användes till konferensartikeln "An iterative approach to determine the refractive index of 3D printed 60GHz PLA lenses" (doi:10.1049/cp.2018.1480).
Se konferensartikeln (metoder) och lapc2018mainfigure.m (databeskrivning - metadata) för detaljer.
Data for: An iterative approach to determine the refractive index of 3D printed 60GHz PLA lenses
Keywords: Lenses; Linser; Manufactured Materials; Tillverkade material; Materials Testing; Materialtestning; Radar; Radar; Physical Sciences; Fysik; Electrical Engineering, Electronic Engineering, Information Engineering; Elektroteknik och elektronik; Materials Engineering; Materialteknik